Warm and Humidified Versus Cold and Dry CO2 Pneumoperitoneum in Minimally Invasive Colon Resection: A Randomized Controlled Trial. (October 2017) - Sutton, Elie; Bellini, Geoffrey; Grieco, Michael J.; Kumara, H. M. C. Shantha; Yan, Xiaohong; Cekic, Vesna; Njoh, Linda; Whelan, Richard L.
Introduction . Peritoneal insufflation with warm-humidified (WH) CO2 gas during minimally invasive surgical procedures is purported to prevent hypothermia and peritoneal desiccation and is associated with decreased postoperative IL-6 levels. This randomized study's purpose was to determine the clinical impact of WH versus cold-dry (CD) CO2 in minimally invasive colon resection (MICR), and to assess perioperative plasma levels of IL-6, TIMP-1, sVEGF-R1, and HSP-70 after MICR. Methods . Operative and short-term clinical data plus perioperative blood samples were collected on MICR patients randomized to receive either WH (36.7°C, 95% humidity) or CD (room temperature, 0% humidity) CO2 perioperatively. Peritoneal biopsies were taken at the start and end of surgery. Outcomes tracked included core temperature, postoperative in-hospital pain levels, analgesia requirements, and standard recovery parameters. Preoperative and postoperative days (PODs) 1 and 3 plasma protein levels were determined via ELISA. Results . A total of 101 patients were randomized to WH CO2 (50) or CD CO2 (51). The WH group contained more diabetics ( P = .03). There were no differences in indication, minimally invasive surgical method used, or core temperature. Pain scores were similar; however, the WH patients required less narcotics on PODs 1 to 3 ( P < .05), and less ketorolac on PODs 1 and 2 ( P < .03). No differences in length of stay, complication rates, or time to flatus/diet tolerance were noted. Plasma levels of the 4 proteins were similar postoperatively. Though insignificant, the WH group had less marked histologic changes on "end-of-case" peritoneal biopsies. Conclusion . This study found significantly lower pain medication requirements for PODs 1 to 3 for the WH group; however, because there were no differences in the pains scores between the groups, firm conclusions regarding WH CO2 cannot be made.